Management of sacrococcygeal pilonidal sinus disease. Issue 2 (15th November 2018) - Harries, Rhiannon L.; Alqallaf, Abdullah; Torkington, Jared; Harding, Keith G.
Abstract : The ideal treatment for patients who suffer from pilonidal sinus disease should lead to a cure with a rapid recovery period allowing a return to normal daily activities, with a low level of associated morbidity. A variety of different surgical techniques have been described for the primary treatment of pilonidal sinus disease and current practice remains variable and contentious. Whilst some management options have improved outcomes for some patients, the complications of surgery, particularly related to wound healing, often remain worse than the primary disease. This clinical review aims to provide an update on the management options to guide clinicians involved in the care of patients who suffer from sacrococcygeal pilonidal sinus disease.